Chemical Constituents in Latent Fingermarks as Indicators of Lifestyle using Gas Chromatography Mass Spectrometry - Vartika Khare; Anu Singla; Shashi Shekhar; Neha Ahirwar (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Fingermarks can be used to pro𿿿le donors by providing details about their gender, age, lifestyle, and interaction with illegal substances. Chemical constituents in the 𿿿ngermarks can reveal signi𿿿cant information about the ngerprint’s origin, which is particularly bene𿿿cial in situations where the donor’s identity is unclear or the print is smudged, deformed or unclear. Aim: To study the exogenous and endogenous substance presentin the𿿿ngermarks of individuals with respect to their lifestyles. Material and Methods: In this study, the latent 𿿿ngermarks donated by42 iividuals of Jhansi, Uttar Pradesh, India were analyzed using Gas Chromatograph Mass Spectrometry to determine the exogenous and endogenous constituents present respectively. Results: Multivariate technique of Principal Component Analysis was applied on the GC data. Further, Hierarchical Cluster Analysis and K means Cluster technique were applied on the results of PCA, to validate the results. PCA showed that the high-dimensional data could be summarized in a few principal components, with the 𿿿rst two components capturing over 27% of he total variance. The biot showed that the samples are not randomly distributed but instead form discernible groups, with some samples being chemically similar and other samples being distinct outliers. K-Means clustering provided a quantitative validation by assigning each sample to one of three distinct clusters, which were consistent with the visual groupings from both the PCA and HCA plots. Conclusion: It can be effectively stated that an individual’s daily lifestyle and occupation have a signficant inÁuence on the exogenous and endogenous constituents of finger mark.